2022
DOI: 10.20524/aog.2022.0686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on the healthcare and psychosocial well-being of patients with inflammatory bowel disease

Abstract: COVID-19 pandemic has resulted in unprecedented disruptions to several aspects of gastroenterology healthcare services worldwide. In particular, patients with inflammatory bowel disease (IBD) represent a sensitive population that must retain access to healthcare services to avoid potential disease exacerbation under the continuous threat of viral infection. Emerging evidence also highlights the severe impact on these patients’ mental well-being, leading to a constant cycle of stress/depression and disease acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Increased stress levels during the pandemic era are particularly of concern in the subpopulation of individuals diagnosed with IBD and/or IBS because stress is a known factor to instigate IBS/IBD symptomatology [4,[8][9][10]. Interestingly, during the pandemic, it was also reported that IBD patients may have been more fearful about COVID-19 infection compared to other individuals [11]. As such, some studies suggested screening specific IBD patients (e.g., females or those aged 50-70 years old), due to their high risk of developing anxiety during the pandemic, which in turn may lead to vicious cycles of anxiety and higher disease activity [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased stress levels during the pandemic era are particularly of concern in the subpopulation of individuals diagnosed with IBD and/or IBS because stress is a known factor to instigate IBS/IBD symptomatology [4,[8][9][10]. Interestingly, during the pandemic, it was also reported that IBD patients may have been more fearful about COVID-19 infection compared to other individuals [11]. As such, some studies suggested screening specific IBD patients (e.g., females or those aged 50-70 years old), due to their high risk of developing anxiety during the pandemic, which in turn may lead to vicious cycles of anxiety and higher disease activity [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during the pandemic, it was also reported that IBD patients may have been more fearful about COVID-19 infection compared to other individuals [ 11 ]. As such, some studies suggested screening specific IBD patients (e.g., females or those aged 50-70 years old), due to their high risk of developing anxiety during the pandemic, which in turn may lead to vicious cycles of anxiety and higher disease activity [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between healthcare providers and patients has always been the cornerstone of healthcare for patients with IBD [ 24 ], and motivational interviewing has emerged as a key strategy for improving therapeutic adherence [ 25 ]. The conceptual framework of motivational interviewing was originally described by William Miller [ 26 ].…”
Section: Introductionmentioning
confidence: 99%